2006
DOI: 10.1002/dc.20525
|View full text |Cite
|
Sign up to set email alerts
|

Cytohormonal and morphological alterations in cervicovaginal smears of postmenopausal women on hormone replacement therapy

Abstract: The objective of the study was to study the cytohormonal and morphological alterations in cervicovaginal smears associated with the use of hormone replacement therapy (HRT) and to assess the utility of vaginal cytology in determining the response to HRT. Ninety postmenopausal women (30 on estrogen-progesterone combination (HRT) for 1 to 24 mo (user 1), 30 on estrogen therapy (ERT) for 1 to 44 mo (user 2), and 30 not on any hormones (nonusers)) were included in the cross-sectional study. Their lateral vaginal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
1
17
0
3
Order By: Relevance
“…Then, for other 14 days, the administration of one suppository per day, one day in one day out. The results showed a marked effect of the tested product on the vaginal dryness and on all other symptoms and signs with statistically significant reductions since the first week of treatment (Gupta et al, 2006). We have also found comparable results with those two trials.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Then, for other 14 days, the administration of one suppository per day, one day in one day out. The results showed a marked effect of the tested product on the vaginal dryness and on all other symptoms and signs with statistically significant reductions since the first week of treatment (Gupta et al, 2006). We have also found comparable results with those two trials.…”
Section: Discussionsupporting
confidence: 79%
“…Consequently, women with atrophic vagina may have problems including sexual dysfunction, pain, bleeding, and loss of vaginal elasticity. The degree of estrogen deficient vaginal atrophy can be evaluated subjectively from the patients' symptoms and/or vaginal examination, and objectively from vaginal pH testing and/or vaginal cytology (van der Laak et al, 2002;Gupta et al, 2006;Nilsson et al, 1995). Brizzolara in the United States found that a vaginal pH > 4 is associated with the increase in number of parabasal cells (≥ 20%) in smears from the proximal to mid vagina.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of finding dysplasia decreases with age [6,7]. The cervical mucosa undergoes morphologic variations with age, and practising cytopathologists must be keenly aware of these differences in order to make accurate diagnoses [8]. Atrophic changes in postmenopausal patients due to lack of estrogenic stimulation can pose diagnostic challenges because they may simulate high-grade dysplasia morphologically [9].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen induces thickening of the vaginal epithelium in postmenopausal women on hormone replacement therapy (14,33) and in ovariectomized macaques (44,45). Additionally, in humans, it also rapidly keratinizes the inner foreskin, the site for HIV entry in the penis (38), and may protect men against HIV.…”
Section: Introductionmentioning
confidence: 99%